(untitled) - Eells, Richard (New York, 1960)
This book has been written as an introduction to the philosophy of a great institution - the modern business corporation. Such a philosophy, when finally matured, will make the corporation more comprehensible and provide norms for corporate performance in a society that relies so heavily upon this remarkable organizational instrument.
Keywords: Corporations,Tổng công ty